Avaliação da resistência ao Cisalhamento de braquetes novos recolocados com diferentes resinas ortodônticas - Jimenez, Emigdio Enrique Orellana (2007)
The present study evaluated in vitro the shear bond strength of new bonded and rebounded metallic brackets with three orthodontic composites. Ninety extracted first superior premolars were randomly divided in three groups, according to the different tested composite. All bonding procedures followed the manufacturer’s specifications with a 300g standard pressure over the bracket during positioning. Alpha plast (AP), Concise (CO) and Transbond XT (TB) were the evaluated composites. For each group, three shear bond strength examinations were performed in three different times, initial (T0), first rebonding (T1) and second rebonding (T2), with a 24 hour interval between them. The tests were performed with a SHIMADZU AG-I, (10KN) machine with a 0,5 mm/min cross-head speed and the fracture strength was recorded in Megapscal (MPa) considering brackets base area. The mean shear bond strength was evaluated and the adhesive remnant index (ARI) was scored. The results showed that in T0 the groups AP and CO presented similar and higher values than TB, in T1 and T2 the highest shear bond strength values were found in group AP, followed by group CO and TB. Those data were submitted to two-way ANOVA and Tukey´s and Bonferroni´s test (p<0,05) and the ARI results were analyzed by the Kruskal Wallis test followed by the Dunn´s test. It was found a statistical significant difference (p<0,05) in shear bond strength between groups but not between the different bonding and rebonding times. The highest shear bond strength values were observed in the group AP, followed by CO and TB. In relation to ARI, it was noticed a significant statistical difference (p<0,05) between the groups, and the TB presented higher values (p<0,05) than those verified in AP and CO, for T0 and T2. It was concluded that repeated bondings with new brackets presented an adhesive difference in shear bond strength considering the utilized composite, however, at bonding and rebonding with the same composite, there are no significant differences.